Leadership and human resource management in improving employee welfare: A literature review - Lintong, Elisabeth Marlina Sari; Bukidz, Danny Philipe (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Leadership plays a very important role in an organization or company. The processes that take place within an organization or company depend on the attitude and leadership style applied. Leadership attitudes and styles in an organization also play an important role in increasing employee satisfaction. Employees who are satisfied with the leadership attitudes implemented by their leaders have the potential to feel appreciated and prosperous. Employee personal well-being is achieved through leadership as a medium. Examining the relationship between leadership and worker well-being as well as the influence of additional factors that bolster it is the aim of this essay. This article examines studies that show a relationship between leadership and worker well-being as well as the mediators and moderators that support that relationship. Using a literature study, the approach looks at leadership philosophies and attitudes in terms of enhancing worker wellbeing. The literature research indicates that there is a noteworthy correlation between employee well-being and leadership. Through intermediate factors, such as welfare forms and leadership styles and processes, leadership may have an impact on employee welfare. Additional findings support the notion that a moderating factor like leadership style might enhance the association between well-being of employees and leadership.